Proceedings 14th International Parallel and Distributed Processing Symposium. IPDPS 2000
DOI: 10.1109/ipdps.2000.845960
|View full text |Cite
|
Sign up to set email alerts
|

Broadcasting in hypercubes in the circuit switched model

Abstract: In this paper, we propose a method which enables us to construct almost optimal broadcast schemes on an n-dimensional hypercube in the circuit switched, -port model. In this model, an initiator must inform all the nodes of the network in a sequence of rounds. During a round, vertices communicate along arc-disjoint dipaths. Our construction is based on particular sequences of nested binary codes having the property that each code can inform the next one in a single round. This last property is insured by a flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a cycle, which is 2-edge connected, there is clearly a log 3 n time protocol. Also, the conjecture was proven to be true for two-dimensional toroidal grids [11] and for hypercubes [1].…”
Section: Conjecture 2 Let G Be a K-edge-connected Undirected Graph mentioning
confidence: 93%
See 1 more Smart Citation
“…In a cycle, which is 2-edge connected, there is clearly a log 3 n time protocol. Also, the conjecture was proven to be true for two-dimensional toroidal grids [11] and for hypercubes [1].…”
Section: Conjecture 2 Let G Be a K-edge-connected Undirected Graph mentioning
confidence: 93%
“…However, it was shown that finding an optimum broadcasting protocol given a general graph is NP-complete [4]. As for specific topologies, efficient protocols were given for trees [3], torus networks [11] and hypercubes [1].…”
Section: Introductionmentioning
confidence: 99%
“…T S (2, 10) (5, 1) (6, 2) (9, 5) (10, 6) (1,9) (2, 10) (5, 1) (6, 2) (9, 5) (10, 6) (1,9) (3, 11) (4, 0) ( …”
Section: Proposition 10 Let S Be a Bidirectional Level Partition Of mentioning
confidence: 99%